Skills-focused lab instruction improves critical thinking skills and experimentation views for all students - Walsh, Cole; Lewandowski, H. J.; Holmes, N. G. (Physical review. Physics education research, 2022)
Instructional labs are fundamental to an undergraduate physics curriculum, but their possible learning goals are vast with limited evidence to support any particular goal. In this study, we evaluate the efficacy of labs with different goals and structures on students' critical thinking skills and views about experimentation, using an extensive database of survey responses from over 20 000 students at over 100 institutions. Here, we show that labs focused on developing experimentation skills improve students' critical thinking skills and experimentation views compared to labs focused on reinforcing lecture concepts. We further demonstrate the positive impacts of skills-based labs over concepts-based labs on these outcomes across students' gender and race or ethnicity. Our analysis also shows that activities to support students' decision making and communication explain over one-half and one-third of the effect of skills-based labs on students' critical thinking skills and experimentation views, respectively, while modeling activities have only a small effect on performance.